2022
DOI: 10.1016/j.wasman.2021.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 lockdown measures on waste production behavior in Lisbon

Abstract: The recent restrictions on mobility and economic activities imposed by governments due to the COVID-19 pandemic have significantly affected waste production and recycling patterns in cities worldwide. This effect differed both between cities and within cities as the measures of confinement adopted by governments had diverse impacts in different areas of cities, depending on their characteristics (e.g., touristic, or residential). In the present work, mixed waste collection areas were created, based on waste co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
(56 reference statements)
3
9
0
Order By: Relevance
“… Urban and Nakada (2021) found that solid waste generation decreased in Brazilian cities when temporary COVID-19 health measures were in effect. A similar decline in waste generation in Lisbon was documented by Sarmento et al (2022) . In contrast, Filho et al (2021a) reported a higher waste generation rate in connection with an increased consumption of packed foods among 204 participants from 23 countries, and an abrupt influx of plastic packaging waste in the residential waste stream ( Filho et al, 2021b ).…”
Section: Literature Reviewsupporting
confidence: 68%
See 1 more Smart Citation
“… Urban and Nakada (2021) found that solid waste generation decreased in Brazilian cities when temporary COVID-19 health measures were in effect. A similar decline in waste generation in Lisbon was documented by Sarmento et al (2022) . In contrast, Filho et al (2021a) reported a higher waste generation rate in connection with an increased consumption of packed foods among 204 participants from 23 countries, and an abrupt influx of plastic packaging waste in the residential waste stream ( Filho et al, 2021b ).…”
Section: Literature Reviewsupporting
confidence: 68%
“…On the other hand, more home cooking with cautious meal planning reduced residential food waste generation during COVID-19 ( Laila et al 2021 a, Rodgers et al 2021 ). A decline in overall waste generation rates is also reported by Urban and Nakada (2021) and Sarmento et al (2022) . These opposing factors likely affected households in different ways, explaining the higher data variabilities in the Group II period.…”
Section: Resultsmentioning
confidence: 81%
“…In a Canadian capital city, a significant increase in residential waste was observed during the early waves of the pandemic ( Richter et al., 2021b ). The reported increase in the residential waste collection during COVID-19 corresponds well with the regulators’ administrative measures restricting business operations and commercial activities ( Zambrano-Monserrate et al., 2020 ; Sarmento et al., 2022 ). The widely adopted work-from-home arrangement, social distancing, restricted traveling, and self-isolation may have also resulted in more residential waste.…”
Section: Introductionsupporting
confidence: 67%
“…(2022) reviewed 9206 papers on smart cities and sustainable development goals (SDG) and found that “waste management” were commonly discussed in SDG studies. Given its significance, many studies have reported the effects of COVID-19 on various waste management issues ( Mahmud et al., 2022 ; Requena-Sanchez et al., 2022 ; Sarmento et al., 2022 ). The literature suggest that the generation and collection of MSW emerged differently under different administrative measures throughout the stages of pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation